Numerical Study of Rosenau-KdV Equation Using Finite Element Method Based on Collocation Approach - Ak, Turgut; Dhawan, Sharanjeet; Karakoc, S. Battal Gazi; Bhowmik, Samir K.; Raslan, Kamal R. (Mathematical Modelling and Analysis, 2017)
In the present paper, a numerical method is proposed for the numerical solution of Rosenau-KdV equation with appropriate initial and boundary conditions by using collocation method with septic B-spline functions on the uniform mesh points. The method is shown to be unconditionally stable using von-Neumann technique. To check accuracy of the error norms L2 and L∞ are computed. Interaction of two and three solitary waves are used to discuss the effect of the behavior of the solitary waves during the interaction. Furthermore, evolution of solitons is illustrated by undular bore initial condition. These results show that the technique introduced here is suitable to investigate behaviors of shallow water waves.